Recent advances in diagnosis, treatment, and prognosis of IgG4-related autoimmune pancreatitis: a narrative review - Xin He; Boyuan Sun; Yuxue Nie; Wen Zhang (Journal of Pancreatology, 2022)
Immunoglobulin G4 (IgG4)-related autoimmune pancreatitis (AIP), also known as “type 1 AIP,” is a rare, chronic, and fibroinflammatory disease manifested as obstructive jaundice and enlargement of the pancreas, usually accompanied by extra-pancreatic organ involvement. The understanding of IgG4-related AIP is gradually deepening. In this review, we summarized the basic concepts, common clinical manifestations, and new progress of the disease including diagnostic, therapeutic strategies, and prognosis mainly based on published case reports, cohort studies, meta-analyses, and guidelines in the past 5 years. Issues such as diagnostic markers, risk factors for relapse, and more effective treatment still need to be further studied.